A Comparison of Two Objective Measures of Binaural Processing: The Interaural Phase Modulation Following Response and the Binaural Interaction Component - Haywood, Nicholas R. (Trends Hear, 2015)
There has been continued interest in clinical objective measures of binaural processing. One commonly proposed measure is the binaural interaction component (BIC), which is obtained typically by recording auditory brainstem responses (ABRs)—the BIC reflects the difference between the binaural ABR and the sum of the monaural ABRs (i.e., binaural − (left + right)). We have recently developed an alternative, direct measure of sensitivity to interaural time differences, namely, a following response to modulations in interaural phase difference (the interaural phase modulation following response; IPM-FR). To obtain this measure, an ongoing diotically amplitude-modulated signal is presented, and the interaural phase difference of the carrier is switched periodically at minima in the modulation cycle. Such periodic modulations to interaural phase difference can evoke a steady state following response. BIC and IPM-FR measurements were compared from 10 normal-hearing subjects using a 16-channel electroencephalographic system. Both ABRs and IPM-FRs were observed most clearly from similar electrode locations—differential recordings taken from electrodes near the ear (e.g., mastoid) in reference to a vertex electrode (Cz). Although all subjects displayed clear ABRs, the BIC was not reliably observed. In contrast, the IPM-FR typically elicited a robust and significant response. In addition, the IPM-FR measure required a considerably shorter recording session. As the IPM-FR magnitude varied with interaural phase difference modulation depth, it could potentially serve as a correlate of perceptual salience. Overall, the IPM-FR appears a more suitable clinical measure than the BIC.